2018
DOI: 10.1002/slct.201801031
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Photosensitizing Properties of Spiro(dipyridinogermole)(dithienogermole)s with Eletron‐Donating Amino and Electron‐Withdrawing Pyridinothiadiazole Substituents

Abstract: Three spiro(dipyridinogermole)(dithienogermole) (sDPyG) derivatives with conjugated substituents on the dithienogermole system were synthesized. sDPyG with highly conjugated dithienylbenzothiadiazole substituents (4) showed moderate photoluminescence (PL) behavior with quantum yields of 15-17%, regardless of the solvent (chloroform, THF, or 1,4dioxane). In contrast, PL quantum yields of sDPyGs with relatively less conjugated triphenylamine and phenylcarbazole substituents, respectively (5 and 6), were decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In addition, DTG has higher chemical stability as compared to DTS, in particular under hydrolytic conditions . These features of DTG permit applications of DTG derivatives in a wide range of optical materials, including sensing materials and photosensitizers for singlet oxygen generation . However, the two substituents on Ge have been limited to simple alkyl chains and substituted phenyl groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DTG has higher chemical stability as compared to DTS, in particular under hydrolytic conditions . These features of DTG permit applications of DTG derivatives in a wide range of optical materials, including sensing materials and photosensitizers for singlet oxygen generation . However, the two substituents on Ge have been limited to simple alkyl chains and substituted phenyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…[29] These features of DTG permit applicationso fD TG derivatives in aw ide range of optical materials,i ncluding sensingm aterials [34,36] and photosensitizers for singlet oxygen generation. [37,38] However,t he two substituents on Ge have been limited to simplea lkyl chains and substituted phenylg roups. This seems to be attributablet ot wo major rea-sons.…”
Section: Introductionmentioning
confidence: 99%
“…Lowering of the PL efficiency by introducing pyridine in the same order as above seemed to reflect the characteristics of bipyridyl that shows no PL in THF at room temperature. 9 The introduction of triarylamine substitution on the thiophene ring efficiently enhanced the conjugation. This is likely due to the intramolecular D−A interaction between the triarylamine donor and the pyridine acceptor, as supported by DFT calculations (vide infra).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“… It is noteworthy that the σ*−π* conjugation is operative even in highly electron-deficient bipyridyl systems, resulting in enhanced electron deficiency of the DPyS and DPyG derivatives compared to noncondensed 4,4′-bipyridyl. It was also demonstrated that spiro­(dipyridinogermole)­(dithienogermole)­s exhibited photosensitizing effects on singlet oxygen generation . Viologen derivatives were also prepared by treating diphenyldipyridinogermole with methyl iodide, and these compounds showed stable electrochromic properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation